2015
DOI: 10.1039/c5cp03886c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Li3O4nano particles in the discharge products of non-aqueous lithium–oxygen batteries leads to lower charge overvoltage

Abstract: Density functional theory calculations are made for bulk thermodynamic properties and surface energies of Li2O2, a primary discharge product, and Li3O4, a possible byproduct in the discharge products, of the non-aqueous lithium-oxygen batteries. Results show that the standard formation Gibbs free energy of bulk Li3O4 is marginally higher than that of Li2O2, but the surface energy of Li3O4 is much lower. Low surface energy results in both lowered nucleation energy and formation Gibbs free energy in the nanomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Yao et al investigated the thermal stabilities of Li 2 O 2 and Li 2 O at the battery working temperature 5. Shi et al reported density functional theory (DFT) calculations and experimental confirmation of Li 3 O 4 nanoparticles as a discharge byproduct 6. Also, the recent discovery of lithium superoxide as a discharge product has attracted much attention, and it is considered as a highly promising candidate for the next‐generation lithium battery 7, 8, 9, 10, 11, 13…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al investigated the thermal stabilities of Li 2 O 2 and Li 2 O at the battery working temperature 5. Shi et al reported density functional theory (DFT) calculations and experimental confirmation of Li 3 O 4 nanoparticles as a discharge byproduct 6. Also, the recent discovery of lithium superoxide as a discharge product has attracted much attention, and it is considered as a highly promising candidate for the next‐generation lithium battery 7, 8, 9, 10, 11, 13…”
Section: Introductionmentioning
confidence: 99%
“…The discharge products in the NiFeO x /CNT electrode were stable and could not be further reduced in Ar (Figure b; Figure S4, Supporting Information), indicating unlikely a mixture of Li 2 O 2 and LiO 2 . The lattice parameters (Table ) and XRD patterns (Figure a; Figure S5, Supporting Information) indicate that the discharge products were not P‐6m2 or P‐3m1 Li 3 O 4 , instead, more likely Li 2 O 2 with Li 2a vacancies. The DFT calculations reveal that the formation of Li 2a vacancies is thermodynamically unfavorable except under LiO 2 ‐rich conditions (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The supersaturation can be calculated according to the relationship Δμ=[ΔGformLinormal2normalOnormal2(T, 1 atm)+zFϕknormalBTlnPnormalO2]where ΔGformLinormal2normalOnormal2 (T, 1 atm) is the free energy for the formation of Li 2 O 2 near the nucleation sites at temperature T and 1 atm, Z is the number of electrons involved in the reactions, F is the Faraday constant, ϕ is the electrochemical potential, k B is the Boltzmann constant, and PnormalO2 is the oxygen pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao's group confirmed the existence of Li 3 O 4 crystal in the discharge product and predicted a low charge overpotential of 0.30 V on (0001) surface of Li 3 O 4 by density functional theory calculation. [44] Later, a series of stable oxygen-rich lithium oxide phases were experimentally synthesized under high pressure and high temperature, including Li 2 O 3 and LiO 4 . [45] The discovery of these new lithium oxides enriches lithium oxide family and may provide alternative choices for stable Li-O 2 battery chemistry.…”
Section: Novel Cathode Redox Chemistrymentioning
confidence: 99%